2012
DOI: 10.1002/pbc.24253
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of models of care for the follow‐up of childhood cancer survivors

Abstract: Follow‐up care for survivors of childhood cancer is increasingly seen as a priority service as numbers of survivors increase. Despite this there are few published evaluations of the available options. We conducted a systematic review of published and unpublished literature. Seven uncontrolled studies, and one comparative study of a related intervention, were identified. Observational data suggest that follow‐up care was useful even for patients who did not perceive this as a need. Suitably powered, well‐conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…In a systematic review of published and unpublished literature, Heirs et al defined that "follow-up care was useful even for patients who did not perceive this as a need" [32]. Inclusion of the regular biennial collection of data from patients using a selfquestionnaire, such as that administered for the American CCSS cohorts [27,33], combined to a regular clinical visit in a multidisciplinary late-effects clinic, would provide greater consistency with regard to the initial study population and sources of data, improve survivor participation in health surveys, and meet the expectations of those patients who desire greater participation in their care and consideration of their opinions by the medical circle.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of published and unpublished literature, Heirs et al defined that "follow-up care was useful even for patients who did not perceive this as a need" [32]. Inclusion of the regular biennial collection of data from patients using a selfquestionnaire, such as that administered for the American CCSS cohorts [27,33], combined to a regular clinical visit in a multidisciplinary late-effects clinic, would provide greater consistency with regard to the initial study population and sources of data, improve survivor participation in health surveys, and meet the expectations of those patients who desire greater participation in their care and consideration of their opinions by the medical circle.…”
Section: Discussionmentioning
confidence: 99%
“…We found transitions were individually tailored such that, even within cancer centers, LTF did not fit neatly into any one care model described in earlier research. 7,43 There was inherent tension around whether and when transfer would result in the best care for their patients. These findings support recommendations of flexible models that suit different contexts and Box 4.…”
Section: Discussionmentioning
confidence: 99%
“…No studies compare effectiveness of these models. 43 Shared care is described as the ideal and is hypothesized to be the most cost-effective; however, the degree to which it actually occurs in practice is not known. 7,15 To develop a health services research agenda informing optimal care models, we conducted qualitative research with LTF providers to examine existing models, as well as successes and challenges in maintaining survivors' connections to care across their transitions to adulthood.…”
mentioning
confidence: 99%
“…A systematic review of several studies, all of which outlined models of long-term follow-up, found that few conclusions could yet be drawn about the most effective models of intervention. 31 The lack of clear answers may drive the need for continued research in this area. 31 …”
Section: Interventions To Reduce Risk Of Treatment-related Cardiotoximentioning
confidence: 99%